2023
DOI: 10.3390/microorganisms11051203
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Crosstalk with Resident Macrophages and Their Role in Invasive Amebic Colitis and Giardiasis—Review

Abstract: The innate immune response is highly dependent on the action of macrophages. They are abundant in the intestine subepithelial lamina propria of the mucosa, where they deploy multiple tasks and play a critical role. The balance between the gut microbiota and M2 macrophages is critical for gut health and homeostasis. Gut microbiota has the power to change macrophage phenotype and replenish the resident macrophage niche during and post infection. As far as the extracellular enteric parasitic infections invasive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…However, the polarization of M1 macrophages will promote the phagocytosis of macrophages, and then kill colon bacillus ( Chen et al, 2023 ). At the same time, the imbalance between gut microbiota and M2 macrophages can affect intestinal health and homeostasis, which may weaken the body’s protection against Giardia infection ( Xaplanteri et al, 2023 ). Some studies have shown that eplerenone can inhibit ILC3, and then prevent the production of IL17, which has a protective effect against giardia infection ( Xaplanteri et al, 2023 ; Zhao et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the polarization of M1 macrophages will promote the phagocytosis of macrophages, and then kill colon bacillus ( Chen et al, 2023 ). At the same time, the imbalance between gut microbiota and M2 macrophages can affect intestinal health and homeostasis, which may weaken the body’s protection against Giardia infection ( Xaplanteri et al, 2023 ). Some studies have shown that eplerenone can inhibit ILC3, and then prevent the production of IL17, which has a protective effect against giardia infection ( Xaplanteri et al, 2023 ; Zhao et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%